Nostalgia for the giant robot: The appropriation of Japanese pop culture in Philippine media - Fondevilla, Herb L. (Journal of Popular Television, The, 2017)
Abstract This article describes the influences of Japanese popular culture on Philippine media through television shows and local advertising. As the generation raised on Japanese animation has grown up, their connection to Japanese culture is presently being manifested through their creative work. As a result, Japanese popular culture has become a part of Philippine nostalgia and is also being used as a powerful marketing tool towards young people. It continues to be prevalent in the Philippines despite having little to no support from the ‘Cool Japan’ project from MOFA. This article analyses a selection of media aired between 2006 and 2014 on Philippine television and YouTube, including television shows, advertisements and music videos, in relation to their visual content, sound and language. Following trends in media allows for a deeper consideration of how globalizing influences can affect local cultures and how these are assimilated, manipulated and eventually used for advertising and marketing.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qcHR2LjUuMi4xNTlfMQ